ACTR-29. A SERIES OF PATIENTS (PTS) WITH RECURRENT GBM (rGBM) TREATED WITH ABT-414, BEVACIZUMAB (BEV) AND CCNU. (11th November 2019) - De Silva, Madhawa; Lee, Adrian; Kastela, Marina; Wheeler, Helen; Khasraw, Mustafa
Abstract: BACKGROUND: ABT-414 showed encouraging results in the phase 2 Intellance 2 rGBM study, but not in the phase 3 Intellance 1 trial, in newly diagnosed EGFR-amplified GBM. We describe a series of pts with rGBM treated with ABT-414 in combination with Bev and CCNU. METHODS: A retrospective review of pts with rGBM receiving ABT-414 with Bev and CCNU. RESULTS: Between 3 and 10/2018, 6 male pts (median age 54y) with EGFR-amplified rGBM were given 1 mg/kg ABT-414 every 3 - 5 weeks (wk) in combination with 10 mg/kg Bev fortnightly. Two pts also received CCNU. Two pts had multifocal disease, and the remainder had left parietal, left frontal, occipital, and right frontal GBMs. All pts were IDH wild-type, and 5 out of 6 were MGMT-unmethylated. Four pts had upfront resection followed by adjuvant therapy, and received between 1 and 8 lines of therapy prior to ABT-414. Median time from chemoradiotherapy to ABT-414 was 34 wk. At time of abstract submission, median duration of therapy was 30 wk (range 5 – 64). Three pts were still alive, 1 on ABT-414 plus Bev, 1 on Bev alone (after ABT-414 + Bev), and 1 on best supportive care. Three pts died after 5, 17, and 42 wk, respectively. All pts developed ocular toxicities, manageable with dose reduction or delays, but no other grade 3 or 4 toxicities. CONCLUSION: ABT-414 with Bev and CCNU was tolerable in this selected small series of pts with EGFR-amplified rGBM, and may have potential activity in selected patients, with 4 out of 6 pts (three MGMT-unmethylated) achieving a PFS greater than 27 wk (range 27 – 64). Despite the outcome of Intellance 1, there may be a subgroup of relapsed pts who benefit from this combination. Further studies are warranted to identify and analyse this group.